Corporate scandals, leadership traits, and governance: insights from indonesian state owned enterprises (2021-2022) - Dedi Permana; Rien Agustin Fadjarenie (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The discourse on Good Corporate Governance (GCG) has increasingly become a focal point in the contemporary business landscape. State-Owned Enterprises (SOEs), as pivotal contributors to the Asian economy, continue to enhance their corporate governance frameworks to meet global standards. However, over the past few years, several Indonesian SOEs have been embroiled in corruption scandals and governance lapses, attracting substantial media scrutiny. This study investigates the impact of Corporate Scandals, Board Nationality, Industry Specialization, and CEO Narcissism on the enhancement of GCG Scores in Indonesian SOEs during the 2021-2022 period. Employing a quantitative research approach, secondary data were extracted from the annual reports of 143 Indonesian SOEs. Through purposive judgment sampling, 79 firms were selected for analysis. The study utilized multiple linear regression analysis via SPSS version 25 to examine the relationships among the variables. The empirical findings reveal that Corporate Scandals, Board Nationality, Industry Specialization, and CEO Narcissism collectively exert a significant influence on GCG Score improvements. Individually, each variable also demonstrates a substantial impact on governance enhancement. Notably, these four factors account for 67% of the variations in GCG Scores, suggesting that the remaining 33% is attributable to other determinants beyond the scope of this study. These results underscore the critical need for Indonesian SOEs to strengthen their governance mechanisms, mitigate unethical corporate practices, and cultivate leadership attributes that align with sound governance principles. Future research should explore additional variables influencing GCG performance to provide a more comprehensive understanding of corporate governance dynamics in emerging markets.